Motivational Strategies in Teaching English as Foreign Language: A Case Study in Junior High School 7 Kuningan - Muhammad Aprianto Budie Nugroho; Nining Mayda (University of Kuningan, 2015)
This research aims to analyze motivational strategies in teaching English as foreign language at 7th grade of Junior High School 7 Kuningan and to analyze students‟ attitudes towards motivational strategies that were applied by teachers in teaching EFL. The researchers used qualitative research by using classroom observation, interview, and questionnaires. The result taken from classroom observation and interview show teacher 1 and teacher 3 applied motivational strategies completely based on the phases of motivational strategies. Thus, the students responded these strategies positively. On the other hand, teacher 2 applied motivational strategies incompletely because the teacher missed the first phases. This was responded negatively by students. Therefore, the students were actively involved in teaching and learning process conducted by teacher 1 and teacher 2, but the students were passively involved in teaching and learning process conducted by teacher 2. Furthermore, the result taken from questionnaires shows that students gave positive attitudes towards the teacher 1 (88.25%), teacher 2 (79.02%), and teacher 3 (85.71%). Based on the findings, it can be concluded that the way the teachers applied motivational strategies in teaching EFL determined students‟ attitudes towards motivational strategies applied by teachers in teaching EFL.Keywords: motivational strategies, phases of motivational strategies, students attitudes, teaching EFL